Good Governance In Golden Visa Policy To Increase Investment And Attract Investors (A Research Study At The Class I Special Immigration Office Tpi Batam) - Rizky Hamonangan Rumapea; Soerya Respationo; Siti Nurkhotijah (Journal of Innovative and Creativity, 2025)
Implementing the Golden Visa policy by the Indonesian government is a strategic step to enhance investment competitiveness and encourage long-term foreign investors into the country, particularly within Special Economic Zones (KEK). In the context of its implementation in Batam City, the Class I Special Immigration Office TPI Batam plays an essential role in carrying out this policy, which should be aligned with the principles of good governance such as transparency, accountability, effectiveness, and legal certainty. This study aims to analyse the legal framework, implementation mechanisms, challenges, and solutions in the implementation of the Golden Visa policy, emphasising the application of good governance by immigration institutions as facilitators of national development. This research uses normative juridical and empirical juridical approaches. The normative approach studies laws and regulations such as Law Number 6 of 2011, Minister of Law and Human Rights Regulation Number 22 of 2023, and Ministry of Finance Regulation Number 82 of 2023. Meanwhile, the empirical approach is obtained through interviews with immigration officials, investors, and Batam's Special Economic Zone authority. The data is analysed using Lawrence M. Friedman's legal system theory as the grand theory, Gustav Radbruch's theory of justice as the middle theory, and Mochtar Kusumaatmadja's legal development theory as the applied theory. The research results show that although the regulations and mechanisms for the Golden Visa policy are already in place, its implementation still faces various obstacles, such as regulatory disharmony, limited human resources, and minimal understanding among foreign investors. Therefore, efforts are needed to harmonise cross-sectoral policies and strengthen digital-based service systems. Applying sound governance principles is key to increasing investor confidence and positioning the Immigration Office as a strategic instrument in supporting national economic development.